Effect of delayed heat treatment on the postharvest characteristics of 'Carabao' mango - Lubaton, Christine Diana S. (Banwa, 2019)
Hot water treatment (HWT) controls postharvest diseases in ‘Carabao’ mango, but delays in treatment could influence fruit quality. In this study, ‘Carabao’ mango fruit were subjected to different heat treatments (Rapid Hot Water Treatment [RHWT] at 60 ℃ for 35-60 sec; HWT, 52-55 ℃ for 5 min; or HWT, 52-55 ℃ for 10 min) within 24 or after 24 h from harvest. Fruit were initially sanitized with 200 ppm sodium hypochlorite and stored in 20 ℃ after heat treatment. Visual quality, peel color, degree of decay, weight loss, total soluble solids (TSS), firmness, days to table ripe stage, days to onset of decay, and shelf life were regularly observed. HWT at 52-55 ℃ for 5 or 10 min extended the shelf life of mango fruit for one and two days, respectively, due to lesser diseases and delayed expression of anthracnose. Time to heat treatment whether within 24 or after 24 h from harvest did not affect disease incidence, but fruit treated within 24 h showed a slight delay in the onset of diseases compared to treatment after 24 h. Except for RHWT, fruit ripening, indicated by color change from green to yellow and time to reach table ripe stage, was hastened by heat treatments, especially in HWT, for 10 min. Rapid ripening of fruit exposed to HWT, indicated also by lower firmness and high TSS at 6 d after treatment, resulted in higher weight loss compared to untreated fruit. HWT can translate to more available visually acceptable and disease-free mangoes in the market.